An on‐site preparable, novel bone‐grafting complex consisting of human platelet‐rich fibrin and porous particles made of a recombinant collagen‐like protein. Issue 5 (1st October 2018) - Tsukioka, Tsuneyuki; Hiratsuka, Takahiro; Nakamura, Masayuki; Watanabe, Taisuke; Kitamura, Yutaka; Isobe, Kazushige; Okudera, Toshimitsu; Okudera, Hajime; Azuma, Akihiko; Uematsu, Kohya; Nakata, Koh; Kawase, Tomoyuki
Abstract: Platelet‐rich fibrin (PRF) is widely used in regenerative medicine. Nonetheless, major issues include its controversial effects on bone regeneration and a lack of quality‐assured glass tubes required for coagulation. We used porous particles (FBG) comprising a recombinant RGD motif‐enriched collagen I‐like protein to activate the coagulation pathway and examined the effects of the resulting PRF–FBG complex on bone regeneration. Human whole‐blood samples were mixed with FBG in plastic tubes and centrifuged to prepare a PRF–FBG complex. Platelet‐derived growth factor‐BB (PDGF‐BB) levels and cell growth activity were determined by ELISA and a bioassay using osteoblasts. Bone regenerative activity was assessed using a mouse model of calvarial bone defect. FBG facilitated PRF‐like matrix formation during centrifugation. In this PRF–FBG complex, the microstructure of fibrin fibers was similar to that of PRF prepared conventionally in glass tubes. PDGF‐BB levels and mitogenic action were not significantly influenced by FBG. In the bone defect model, although PRF did not exert any significant positive effects on its own, in combination with FBG, it synergistically stimulated new bone formation. This study demonstrated that incorporation of FBG into whole‐blood samples induces PRF formation without the aid of glass tubes. The resulting PRF–FBG complex could be a promising bone grafting material in clinical settings. © 2018 The Authors. Journal of Biomedical Materials Research Part B: Applied Biomaterials published by Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1420–1430, 2019.